Modelling effects of different milk production intensities on methane production and nitrogen excretion when targeted amounts of milk and beef are produced - Huuskonen, Arto; Manni, Katariina; Huhtanen, Pekka (Agricultural and Food Science, 2025)
The objective of the study was to model the effects of different milk production intensities on methane (CH4) production and nitrogen (N) excretion of cattle in Finnish milk and beef production when the targeted amount of milk and beef is produced. Beef production strategies at current annual milk production in Finland (2 200 million kg) were optimised by Excel Solver for each combination of milk yield (8 000, 9 000, 10 000, 11 000, and 12 000 kg year-1) and beef production (60, 65, 70, 75, 80, 85, 90, 95, and 100 million kg year-1). Increased milk production intensity decreased total CH4 production at each beef production level. In addition, at the lower levels of beef production than currently (85 million kg) total manure N output decreased with increased intensity of milk production but at current or higher beef production levels the effects of milk yield were small. The current strategy of producing milk and beef with high milk production intensity seems to be effective in terms of CH4 production and N emissions.
Keywords: maidontuotanto (kotieläintuotanto); naudanlihantuotanto; ympäristövaikutukset; dairy cattle; beef cattle; beef production; environmental impacts